The influence of marketing strategies on consumer loyalty for agricultural retail stores - Bogacwi, Lerato (University of the Free State, 2017)
The main focus is on agricultural retail stores and on how these stores can retain the current market share they have and improve on gaining an even bigger market share. The study focused on 12 main attributes with their main marketing strategies to achieve customer loyalty. This study alternated between a descriptive and an explorative type of research, using the qualitative method describing the agricultural sector. The structured questionnaires, comprising closed-ended questions were distributed in all the focus areas of the nine provinces of South Africa. Even though not all provinces responded this study is significant and could assist further researches with a base framework to build from or create a better framework for the implementation in the industry. The results of this study will assist cooperatives and the new-generation cooperatives, as well as agribusinesses to improve where is needed to achieve better customer loyalty and to achieve a competitive advantage. The agricultural retail stores are competing not only among themselves but also with big hyper- and superstores. Customers are moving towards the “one-stop-shop” concept where they can purchase all their goods in one place. Agricultural stores can use this to their advantage. New business opportunities like online catalogues and sending customers and members special alerts and notifications are vital as customers are now becoming more technologically minded. Keeping customers and members informed will work to the benefit of the store. Building lasting relationships through innovative memberships and social media would increase the profitability of the agricultural retail store. This study is significant to the management within cooperatives in South Africa to provide them with a model to implement and assist their individual organisations to achieve or support competitiveness.
Dissertation (M.Sc.Agric. (Agricultural Economics))--University of the Free State, 2017
Keywords: Marketing -- Management; Retail trade; Customer loyalty; Consumer satisfaction